Student’s knowledge of covid-19 positive postpartum mother’s care - suryani hartati halim (Jurnal Keperawatan, 2022)
Introduction: An overview of student knowledge about positive postpartum maternal care for COVID-19, characterized by an acute respiratory infection (ARI) with symptoms of fever, cough, shortness of breath, sore throat, runny nose, and mild pneumonia. This study aimed to determine student knowledge about postpartum COVID-19 care in the hospital. Objectives: This study aimed to describe nursing academy students' knowledge of the care of positive covid 19 postpartum mothers. Methods: This descriptive study has a cross-sectional design. Fifty-seven students were selected as participants by consecutive sampling technique. This study was conducted from August to December 2020. Result: The result of this study found that most were 19-20 years of age, and the factor questionnaire that was most associated with good knowledge was that students in semester 5 were 9.5% interested in maternity nursing at 8.3%. Conclusion: Most older students aged 19-20 have sufficient knowledge, namely 60.5%, about the care of postpartum mothers who are Covid-19 positive.